Re-design do medicamento allestra 20 - Quintas, Thiago Tavares (2013)
This project aims to improve the packaging of contraception medication Allestra 20 three blister packs of 21 dragees produced by the company Ache. The current package has excess parts that cause a greater financial cost, both in spending onraw materials as well as in the whole process of logistics storage and transportation, as well as generating a greater volume of trash and consequently harm the environment . With the implementation of the project re-design is intended to offer thepossibility of applying new materials and also a new format that contributes to the problems exposed. To this end, the project must also consider the interface that the user has with the product in order to optimize it, but not distort this relationship.